ALPHA-GST AS A TUBULAR BIOMARKER IN EARLY DIAGNOSIS OF ACUTE KIDNEY INJURY IN CARDIAC SURGERY. (April 2021) - Santos, Ana Carolina Casinhas Dos; Matos, Andreia; Raimundo, Mário; Madureira, Ana Isabel; Malcato, Ester; Côrte-Real, Hugo; Gameiro, Joana; Nobre, Ângelo; Bicho, Manuel; Almeida, Edgar
Abstract : Objective: Acute Kidney Injury(AKI) is a frequent complication in cardiac surgery, leading to an increase in morbility/mortality. The monitorization of the creatinine after the procedure is recommended, however, new tubular biomarkers may allow earlier diagnosis of AKI(a few hours after the procedure, against the 24/48 hours standard). Glutathione S-transferase(GST), cytoplasmic enzymes involved in detoxification of free radicals, are presented in the proximal contoured tube. The aim of this study is to evaluate the use of a single alpha-GST determination at 3 h after surgery, to early diagnosis of AKI. Design and method: Cohort, prospective and observational study, with adults submitted to elective cardiac surgery (valvular/coronary), without chronic kidney disease. Blood and urine samples were collected simultaneously before(T0) and within 3 hours after surgery(T1). The levels of alpha-GST were determined in the urine samples by ELISA and normalized to urinary creatinine(UCr). The variation of alpha-GST was calculated using the difference between T1 and T0(T1-T0). Demographic, clinical and surgical-related data was collected. For statistical analysis, Chi-square and Mann-Whitney test were used. The ROC curve was generated in order to evaluate the discriminative power of the biomarker. P < 0.05 was statistically significant. Results: This study included 17 patients(11 male and 6 female), with 88.2% submitted to valvular surgery, with a mean age of 63.4 ± 14.3 years. Before the procedure, 82.4% of the patients had hypertension. After 48 hours surgery, using as gold standard the KDIGO classification, 6 patients presented AKI stage 1(75%) and 2(25%) stage 2. The mean arterial blood pressure was higher before surgery(T0: 90.0[74.5–103.3] vs T1: 64.5[57.2–80.7], p = 0.05). The increase of alpha-GST levels were associated to presence of AKI(p = 0.05). This increase remains when associated with the variation of alpha-GST(T1-T0) without and with AKI (- 0, 002[-0.02–0.004]vs -0.02[0.009–0.04], respectively, p = 0.003). In the ROC curve, this variation had a AUC = 0.958(p = 0.05) and AUC = 0.854(p = 0.028) for the cut-off of the alpha-GST variation. These biomarkers present 78%-specificity and 75%-sensibility. Conclusions: alpha-GST is a promising biomarker to the early diagnosis of AKI after cardiac surgery with only one determination, contributing to this diagnosis before an increase of serum creatinine. Preventing costs and therapeutic options.